High-entropy alloy / ceramic combined superhard composite material and preparation method thereof
By using high-entropy alloys and non-stoichiometric carbides and WC as binding agents and performing discharge plasma sintering with diamond or cBN, the problems of toughness regulation and sintering temperature reduction of superhard composites are solved, and the preparation of superhard composites with high-entropy alloy/ceramic combination with performance close to traditional superhard materials is achieved.
Patent Information
- Application Number
- CN202510037382.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-04
AI Technical Summary
Existing superhard composites have challenges in regulating strength and toughness and reducing sintering temperature, and are costly to produce.
High entropy alloys (HEAs) CoCrNiCuFe, AlZnCuFeTi and CoNiCuFeMn are used as binders, combined with non-stoichiometric carbides (TiC0.4 and VC0.5) and WC as binders, discharge plasma sintering is performed with diamond or cBN, and the bonding agent ratio, powder preparation process and sintering parameters are optimized.
A high-entropy alloy/ceramic combination superhard composite material with a performance close to that of traditional superhard materials is prepared, which improves the mechanical, corrosion resistance and high temperature resistance of the material, while reducing sintering temperature and production costs.
Smart Images

Figure CN119753475A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of superhard composite materials, and in particular to a high entropy alloy / ceramic combined superhard composite material and a preparation method thereof. Background Art
[0002] Ultra-thin cutting blades are mainly used for cutting and processing precision and precious products. They are widely used in silicon wafers, precision ceramics, gemstones, optical glass, LED substrates, optical components and other fields. Compared with traditional cutting tools, they have the characteristics of less cutting loss, good cutting surface flatness, good finish, and high cutting efficiency. At present, the most commonly used metal-bonded ultra-thin cutting blades on the market are relatively mature in China, but most of them are products with low cutting efficiency and poor cutting quality. They cannot be used at all on some very thin and tough products. Although ceramic ultra-thin cutting blades can solve the problems of low cutting efficiency and short life, they are very brittle and can easily disintegrate during the cutting process. In addition, high entropy alloys (HEAs) have advantages that traditional alloys cannot match, such as high strength, high work hardening, high temperature softening resistance and high temperature oxidation resistance. When used to replace traditional metals as a bonding phase, it can effectively improve material properties. The present invention studies how to use HEAs, WC and non-stoichiometric carbides as binders, and perform composite sintering with diamond or cBN to prepare a high entropy alloy / ceramic combined superhard composite material, and optimize the binder ratio, powder preparation process and sintering parameters to solve the irreconcilable contradiction between the strength and toughness of superhard materials, and prepare a high entropy alloy / ceramic combined superhard composite material comparable to traditional superhard materials. Summary of the invention
[0003] According to the above-mentioned technical problems of how to improve the toughness of super-hard composite materials, reduce the sintering temperature and reduce the production cost, the present invention provides a super-hard composite material of high entropy alloy / ceramic combination and its preparation method. The present invention mainly adopts different types of HEAs (CoCrNiCuFe, AlZnCuFeTi and CoNiCuFeMn) as binders, and introduces non-stoichiometric carbides (TiC0.4 and VC0.5) as modified additives, and WC as binders, and uses a method of spark plasma sintering with diamond or cBN to prepare a super-hard composite material of high entropy alloy / ceramic combination, wherein the metal elements Co, Ni and Fe are all common binders or important additives, and have good wettability to WC and diamond; the addition of low melting point metal elements Cu, Al and Zn is used to reduce the melting temperature of the alloy; the addition of strong carbide forming element Ti gives HEAs higher strength and hardness; the introduction of Cr and Mn can improve the oxidation resistance and inhibit grain growth respectively. The vacancy effect introduced by the stoichiometric carbide can accelerate the mutual diffusion of atoms, promote the occurrence of interface reactions, and improve the sintering performance of superhard materials. Using the two as a composite binder can combine the advantages, improve the performance of high entropy alloy / ceramic combined superhard composite materials, and reduce sintering problems.
[0004] The technical means adopted by the present invention are as follows: 1. A high entropy alloy / ceramic combined superhard composite material, the composition of the composite material in percentage is: CoCrNiCuFe accounts for 5-15wt.%, 3-10wt.%VC0.5 and 70-90wt.%WC, and the balance is diamond / cBN. The particle size of the above-mentioned CoCrNiCuFe is 150nm or less; the purity of WC is>99%, the particle size is 150nm or less, and the particle size of diamond is 28μm. The high entropy alloy raw material is CoCrNiCuFe, AlZnCuFeTi and CoNiCuFeMn high entropy alloy powders in equal molar ratios, and the non-stoichiometric carbide raw material is any one of TiC0.4 and VC0.5 powders prepared by mechanical alloying method or Ti and TiC mixed powders prepared by rolling wet grinding method and V and VC mixed powders.
[0005] The present invention also discloses a method for preparing the above-mentioned high entropy alloy / ceramic combined superhard composite material, comprising the following steps: S1, preparation of high entropy alloy S2, preparation of non-stoichiometric carbide, S3, mixing S4, spark plasma sintering, wherein: S1. Preparation of CoCrNiCuFe powder: In a glove box filled with argon, Co, Cr, Ni, Cu and Fe were mixed in a molar ratio of 1:1:1:1:1 and loaded into a WC carbide ball mill. The ball-to-material mass ratio was 10:1. The rotation speed was 300-600 r / min. The ball milling time was 20-50 h. The mill was stopped for 30 min every 5 h to dissipate heat. The raw materials adhering to the grinding balls and the inner wall of the mill were scraped off and mixed after stopping every 10 h. The milling was continued to obtain CoCrNiCuFe powder with a particle size of 150 nm or finer. S2. Preparation of VC0.5 powder: In a glove box filled with argon, VC powder and V powder were loaded into a WC carbide ball mill at a mass ratio of 55.3:44.7, with a ball to material mass ratio of 10:1 to 20:1, a rotation speed of 450 r / min, a ball milling time of 60 h, and a 30-min stop for heat dissipation every 5 h to obtain VC0.5 powder; S3, mixing: in a glove box filled with argon, weigh 5-15wt.% of the CoCrNiCuFe powder prepared in step S1, add it to 3-10wt.% VC0.5 powder and 70-90wt.% WC powder prepared in step S2, and then ball mill the mixture for 1-5 hours, then add 1-5wt.% diamond / cBN powder, the ball-to-material mass ratio is 5:1-10:1, the rotation speed is 200-400r / min, the ball milling time is 2-5h, and the mill is stopped for 10min for heat dissipation every 1h; S4, sintering preparation: the mixed material obtained in step S3 is loaded into a graphite mold for pre-compression, the pre-compression pressure is 10-30 MPa, and the pre-compression is 60S; then spark plasma sintering is performed, the vacuum degree is 40Pa, the sintering pressure is 30-40MPa, the sintering temperature is 1000-1350°C, the heating rate is 30-100°C / min, and the holding time is 3-30min; then the temperature is reduced and the pressure is released to obtain a superhard composite material combined with a high entropy alloy / ceramic.
[0006] Furthermore, according to the preparation method described in step 2, the particle size of the V powder is 1-3 μm, and the purity is >99%, and the particle size of the VC powder is <45 μm, and the purity is >99%.
[0007] Furthermore, according to the preparation method described in step one, the purity of the Co, Cr, Ni, Cu, and Fe powders is >99%, wherein the particle size of the Co powder is 1-3 μm, the particle size of the Cr powder is <75 μm, and the particle size of the remaining metal element powders is <45 μm.
[0008] Furthermore, according to the preparation method described in step three, the particle size of the WC powder is 1-3 μm and the purity is >99%.
[0009] Furthermore, according to the preparation method described in step three, the ball milling processes of steps S1, S2 and S3 all use three large, medium and small sizes of WC cemented carbide balls with diameters of 8 mm, 5 mm and 2 mm respectively, among which the mass ratio of large, medium and small sizes of WC cemented carbide balls is 6:3:1.
[0010] Further, according to the preparation method described in step four, the specific sintering process in step S4 is: first, slowly apply pressure to the sample to 40-50MPa; then, evacuate to 40Pa; then, heat from room temperature to 600°C in 5 minutes, and keep at 600°C for 10 minutes; then increase the temperature from 600°C to 1000-1350°C at a heating rate of 30-100°C / min, and keep warm for 3-30 minutes; cool with the furnace to obtain a blank; perform surface grinding and deburring on the prepared blank to obtain a superhard composite material combined with a high entropy alloy / ceramic.
[0011] Compared with the prior art, the present invention has the following advantages: 1. The present invention selects three phase structures of HEAs as binders, among which CoCrNiCuFe powder prepared by mechanical alloying method presents FCC+BCC dual-phase structure, AlZnCuFeTi powder presents amorphous structure with incompletely dissolved Ti element, and CoNiCuFeMn powder presents FCC structure. The sintered bodies all have excellent comprehensive properties, which exceed the traditional metal binders such as Co, Ni, Fe, etc., and can improve the mechanical, corrosion resistance and high temperature resistance of superhard materials. The selected HEAs contain trace amounts of Co or no Co, which meets the requirements of "removing Co and replacing Co" and can reduce production costs.
[0012] 2. The present invention provides a process technology for preparing a superhard composite material of high entropy alloy-ceramic binder by mechanical alloying and spark plasma sintering. The prepared cemented carbide has excellent comprehensive mechanical properties, simplifies the preparation process, and can be suitable for industrial production.
[0013] 3. The addition of non-stoichiometric carbides not only inhibits the growth of WC grains, but also utilizes the vacancy effect to promote the diffusion solid solution reaction between the metal components with low alloying rate in HEAs and TiC0.4 or VC0.5, thereby achieving a modification effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings: Figure 1 is the XRD pattern of different high entropy alloy powders; Figure 2is a microstructure morphology diagram of the composite sintered body in Example 4; Figure 3 is a microstructure morphology diagram of the composite sintered body in Example 5; Figure 4 This is the microstructure morphology of the diamond composite sintered body in Example 6. DETAILED DESCRIPTION
[0015] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0016] It should be noted that the terms used here are only for describing specific embodiments, and are not intended to limit exemplary embodiments according to the present invention. In addition, it should also be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates that there are features, steps, operations, devices, components and / or combinations thereof. Unless otherwise specifically stated, the relative arrangement of the parts and steps described in these embodiments, numerical expressions and numerical values do not limit the scope of the present invention. The technology, methods and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but in appropriate cases, the technology, methods and equipment should be regarded as part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar reference numerals and letters represent similar items in the following figures, so once a certain item is defined in one figure, it does not need to be further discussed in the subsequent figures.
[0017] The detection equipment described in the present invention are all instruments used in conventional detection means, such as X-ray diffractometer, Vickers hardness tester, apparent porosity density tester, scanning electron microscope, assembled material surface and interface performance tester, etc.
[0018] A high entropy alloy / ceramic combined superhard composite material, the percentage composition of the composite material is: CoCrNiCuFe accounts for 5-15wt.%, 3-10wt.%VC 0.5and 70-90wt.% WC, the balance is diamond / cBN; wherein the particle size of CoCrNiCuFe is less than 150nm; the purity of WC is greater than 99%, the particle size is less than 150nm, and the particle size of diamond is 28μm; the high entropy alloy raw material is CoCrNiCuFe, AlZnCuFeTi and CoNiCuFeMn high entropy alloy powders in equal molar ratio, and the non-stoichiometric carbide raw material is TiC prepared by mechanical alloying method 0.4 and VC 0.5 Any one of Ti and TiC mixed powder and V and VC mixed powder prepared by powder or rolling wet grinding method.
[0019] A method for preparing a high entropy alloy / ceramic combined superhard composite material comprises the following steps: S1, preparation of a high entropy alloy, S2, preparation of a non-stoichiometric carbide, S3, mixing, S4, spark plasma sintering, wherein: S1. Preparation of CoCrNiCuFe powder: In a glove box filled with argon, Co, Cr, Ni, Cu and Fe were mixed in a molar ratio of 1:1:1:1:1 and loaded into a WC carbide ball mill. The ball-to-material mass ratio was 10:1. The rotation speed was 300-600 r / min. The ball milling time was 20-50 h. The mill was stopped for 30 min every 5 h to dissipate heat. The raw materials adhering to the grinding balls and the inner wall of the mill were scraped off and mixed after stopping every 10 h. The milling was continued to obtain CoCrNiCuFe powder with a particle size of 150 nm or finer. S2、VC 0.5 Powder preparation: VC powder and V powder were loaded into a WC carbide ball mill in a glove box filled with argon gas at a mass ratio of 55.3:44.7, with a ball-to-material mass ratio of 10:1-20:1, a rotation speed of 450 r / min, a ball milling time of 60 h, and a 30-min stop for heat dissipation every 5 h to obtain VC 0.5 powder; S3, mixing: in a glove box filled with argon, weigh 5-15wt.% of the CoCrNiCuFe powder prepared in step S1, add 3-10wt.% of VC prepared in step S2, 0.5 The powder and 70-90wt.% WC powder are ball-milled for 1-5 hours, and then 1-5wt.% diamond / cBN powder is added, the ball-to-material mass ratio is 5:1-10:1, the rotation speed is 200-400r / min, the ball milling time is 2-5h, and the machine is stopped for 10min for heat dissipation after every 1h of rotation; S4, sintering preparation: the mixed material obtained in step S3 is loaded into a graphite mold for pre-compression, the pre-compression pressure is 10-30 MPa, and the pre-compression is 60S; then spark plasma sintering is performed, the vacuum degree is 40Pa, the sintering pressure is 30-40MPa, the sintering temperature is 1000-1350°C, the heating rate is 30-100°C / min, and the holding time is 3-30min; then the temperature is reduced and the pressure is released to obtain a superhard composite material combined with a high entropy alloy / ceramic.
[0020] Furthermore, the particle size of the V powder is 1 to 3 μm, and the purity is >99%, and the particle size of the VC powder is <45 μm, and the purity is >99%.
[0021] Furthermore, the purity of Co, Cr, Ni, Cu and Fe powders is >99%, wherein the particle size of Co powder is 1-3 μm, the particle size of Cr powder is <75 μm, and the particle size of other metal element powders is <45 μm.
[0022] Furthermore, the particle size of the WC powder is 1 to 3 μm, and the purity is >99%.
[0023] Furthermore, the ball milling processes of steps S1, S2 and S3 all use three types of large, medium and small WC carbide balls with diameters of 8 mm, 5 mm and 2 mm, respectively, wherein the mass ratio of the large, medium and small WC carbide balls is 6:3:1.
[0024] Furthermore, the specific sintering process in step S4 is: first, slowly apply pressure to the sample to 40-50MPa; then, evacuate to 40Pa; then, heat from room temperature to 600°C in 5 minutes, and keep at 600°C for 10 minutes; then increase the temperature from 600°C to 1000-1350°C at a heating rate of 30-100°C / min, and keep warm for 3-30 minutes; cool with the furnace to obtain a blank; perform surface grinding and deburring on the prepared blank to obtain a superhard composite material of high entropy alloy / ceramic combination.
[0025] Therefore, 6 groups of examples with different proportions were carried out according to the above method. Example 1
[0026] As shown in Table 1, for the preparation of VC 0.5 As shown in Table 2, the raw material ratio of the cBN composite material in Example 1 is as follows:
[0027]
[0028] S1. Add 0.2 ml of industrial ethanol as a dispersant to the raw material powder consisting of 5.53 g of vanadium carbide powder and 4.47 g of vanadium powder, and put it into a cemented carbide tank. The ball-to-material ratio is 10:1. The ball milling medium is a cemented carbide ball with a diameter of 8 mm and 5 mm. After repeated gas washing in the transition chamber of the glove box, put it into the operating chamber of the ball mill. The gas used is argon. Cover the sealing cover to ensure that the tube is in an argon environment. Take it out and put it into the ball mill. The gas used is argon. Cover the sealing cover to ensure that the tube is in an argon environment. Take it out and put it into the ball mill. The ball milling speed is 450 r / min, and it rotates for 60 min each time. Stop for 20 min to dissipate heat. After ball milling for 60 h, VC 0.5 ; S2. In a glove box filled with argon, Co, Cr, Ni, Cu and Fe were mixed in a molar ratio of 1:1:1:1:1 and loaded into a WC cemented carbide ball mill. The ball-to-material mass ratio was 10:1. The rotation speed was 400 r / min and the ball milling time was 30 h. The mill was stopped for 30 min every 5 h to dissipate heat. The raw materials adhering to the grinding balls and the inner wall of the mill were scraped off and mixed every 10 h. Then, the milling was continued to obtain CoCrNiCuFe powder with a particle size of 150 nm or more. S3, mixing: In a glove box filled with argon, weigh 0.956 g of the CoCrNiCuFe powder prepared in step S1, add 0.413 g of VC prepared in step S2, 0.5 After the powder and 8.317 g WC powder were ball-milled for 1 hour, 0.297 g cBN powder was added, the ball-to-material mass ratio was 10:1, the rotation speed was 350 r / min, and the ball-milling time was 1 hour; S4, sintering preparation: the mixed material obtained in step S3 is loaded into a graphite mold for pre-compression, the pre-compression pressure is 30 MPa, and the pre-compression is 60 s; then spark plasma sintering is performed, the vacuum degree is 40 Pa, the sintering pressure is 30 MPa, the sintering temperature is 1150 ℃, the heating rate is 50 ℃ / min, and the holding time is 10 min; then the temperature is reduced and the pressure is released to obtain a high entropy alloy / ceramic combined cubic boron nitride composite material.
[0029] The high entropy alloy / ceramic cBN composite material sample after spark plasma sintering was polished and then tested for structure and performance. The technical parameters of the obtained sintered block are as follows: Example 2
[0030] The raw material formula is weighed according to the following percentages:
[0031] S1. Add 0.2 ml of industrial ethanol as a dispersant to the raw material powder consisting of 5.53 g of vanadium carbide powder and 4.47 g of vanadium powder, and put it into a cemented carbide tank. The ball-to-material ratio is 10:1. The ball milling medium is a cemented carbide ball with a diameter of 8 mm and 5 mm. After repeated gas washing in the transition chamber of the glove box, put it into the operating chamber of the ball mill. The gas used is argon. Cover the sealing cover to ensure that the tube is in an argon environment. Take it out and put it into the ball mill. The gas used is argon. Cover the sealing cover to ensure that the tube is in an argon environment. Take it out and put it into the ball mill. The ball milling speed is 450 r / min, and it rotates for 60 min each time. Stop for 20 min to dissipate heat. After ball milling for 60 h, VC 0.5 ; S2. In a glove box filled with argon, Co, Cr, Ni, Cu and Fe were mixed in a molar ratio of 1:1:1:1:1 and loaded into a WC cemented carbide ball mill. The ball-to-material mass ratio was 10:1. The rotation speed was 400 r / min and the ball milling time was 30 h. The mill was stopped for 30 min every 5 h to dissipate heat. The raw materials adhering to the grinding balls and the inner wall of the mill were scraped off and mixed every 10 h. Then, the milling was continued to obtain CoCrNiCuFe powder with a particle size of 150 nm or more. S3, mixing: In a glove box filled with argon, weigh 0.956 g of the CoCrNiCuFe powder prepared in step S1, add 0.413 g of VC prepared in step S2, 0.5 After the powder and 8.317 g WC powder were ball-milled for 1 hour, 0.297 g cBN powder was added, the ball-to-material mass ratio was 10:1, the rotation speed was 350 r / min, and the ball-milling time was 1 hour; S4, sintering preparation: the mixed material obtained in step S3 is loaded into a graphite mold for pre-compression, the pre-compression pressure is 30 MPa, and the pre-compression is 60 s; then spark plasma sintering is performed, the vacuum degree is 40 Pa, the sintering pressure is 30 MPa, the sintering temperature is 1250 ℃, the heating rate is 50 ℃ / min, and the holding time is 10 min; then the temperature is reduced and the pressure is released to obtain a high entropy alloy / ceramic combined cubic boron nitride composite material.
[0032] The high entropy alloy / ceramic cBN composite material sample after spark plasma sintering was polished and then tested for structure and performance. The technical parameters of the obtained sintered block are as follows: Example 3
[0033] The raw material formula is weighed according to the following percentages:
[0034] S1. Add 0.2 ml of industrial ethanol as a dispersant to the raw material powder consisting of 5.53 g of vanadium carbide powder and 4.47 g of vanadium powder, and put it into a cemented carbide tank. The ball-to-material ratio is 10:1. The ball milling medium is a cemented carbide ball with a diameter of 8 mm and 5 mm. After repeated gas washing in the transition chamber of the glove box, put it into the operating chamber of the ball mill. The gas used is argon. Cover the sealing cover to ensure that the tube is in an argon environment. Take it out and put it into the ball mill. The gas used is argon. Cover the sealing cover to ensure that the tube is in an argon environment. Take it out and put it into the ball mill. The ball milling speed is 450 r / min, and it rotates for 60 min each time. Stop for 20 min to dissipate heat. After ball milling for 60 h, VC 0.5 ; S2. In a glove box filled with argon, Co, Cr, Ni, Cu and Fe were mixed in a molar ratio of 1:1:1:1:1 and loaded into a WC cemented carbide ball mill. The ball-to-material mass ratio was 10:1. The rotation speed was 400 r / min and the ball milling time was 30 h. The mill was stopped for 30 min every 5 h to dissipate heat. The raw materials adhering to the grinding balls and the inner wall of the mill were scraped off and mixed every 10 h. Then, the milling was continued to obtain CoCrNiCuFe powder with a particle size of 150 nm or more. S3, mixing: In a glove box filled with argon, weigh 0.956 g of the CoCrNiCuFe powder prepared in step S1, add 0.413 g of VC prepared in step S2, 0.5 After the powder and 8.317 g WC powder were ball-milled for 1 hour, 0.297 g cBN powder was added, the ball-to-material mass ratio was 10:1, the rotation speed was 350 r / min, and the ball-milling time was 1 hour; S4, sintering preparation: the mixed material obtained in step S3 is loaded into a graphite mold for pre-compression, the pre-compression pressure is 30 MPa, and the pre-compression is 60 s; then spark plasma sintering is performed, the vacuum degree is 40 Pa, the sintering pressure is 30 MPa, the sintering temperature is 1300 ℃, the heating rate is 50 ℃ / min, and the holding time is 10 min; then the temperature is reduced and the pressure is released to obtain a high entropy alloy / ceramic combined cBN composite material.
[0035] The high entropy alloy / ceramic cBN composite material sample after spark plasma sintering was polished and then tested for structure and performance. The technical parameters of the obtained sintered block are as follows: Example 4
[0036] The raw material formula is weighed according to the following percentages:
[0037] S1. Add 0.2 ml of industrial ethanol as a dispersant to the raw material powder consisting of 5.53 g of vanadium carbide powder and 4.47 g of vanadium powder, and put it into a cemented carbide tank. The ball-to-material ratio is 10:1. The ball milling medium is a cemented carbide ball with a diameter of 8 mm and 5 mm. After repeated gas washing in the transition chamber of the glove box, put it into the operating chamber of the ball mill. The gas used is argon. Cover the sealing cover to ensure that the tube is in an argon environment. Take it out and put it into the ball mill. The gas used is argon. Cover the sealing cover to ensure that the tube is in an argon environment. Take it out and put it into the ball mill. The ball milling speed is 450 r / min, and it rotates for 60 min each time. Stop for 20 min to dissipate heat. After ball milling for 60 h, VC 0.5 ; S2. In a glove box filled with argon, Co, Cr, Ni, Cu and Fe were mixed in a molar ratio of 1:1:1:1:1 and loaded into a WC cemented carbide ball mill. The ball-to-material mass ratio was 10:1. The rotation speed was 400 r / min and the ball milling time was 30 h. The mill was stopped for 30 min every 5 h to dissipate heat. The raw materials adhering to the grinding balls and the inner wall of the mill were scraped off and mixed every 10 h. Then, the milling was continued to obtain CoCrNiCuFe powder with a particle size of 150 nm or more. S3, mixing: in a glove box filled with argon, weigh 0.4859 g of the CoCrNiCuFe powder prepared in step S1, add 0.4616 g of VC prepared in step S2 0.5 After the powder and 8.7727 g WC powder were ball-milled for 1 hour, 0.27986 g cBN powder was added, the ball-to-material mass ratio was 10:1, the rotation speed was 350 r / min, and the ball-milling time was 1 hour; S4, sintering preparation: the mixed material obtained in step S3 is loaded into a graphite mold for pre-compression, the pre-compression pressure is 30 MPa, and the pre-compression is 60 s; then spark plasma sintering is performed, the vacuum degree is 40 Pa, the sintering pressure is 30 MPa, the sintering temperature is 1300 ℃, the heating rate is 50 ℃ / min, and the holding time is 10 min; then the temperature is reduced and the pressure is released to obtain a high entropy alloy / ceramic combined cBN composite material.
[0038] The high entropy alloy / ceramic cBN composite material sample after spark plasma sintering was polished and then tested for structure and performance. The technical parameters of the obtained sintered block are as follows: Example 5
[0039] The raw material formula is weighed according to the following percentages:
[0040] S1. Add 0.2 ml of industrial ethanol as a dispersant to the raw material powder consisting of 5.53 g of vanadium carbide powder and 4.47 g of vanadium powder, and put it into a cemented carbide tank. The ball-to-material ratio is 10:1. The ball milling medium is a cemented carbide ball with a diameter of 8 mm and 5 mm. After repeated gas washing in the transition chamber of the glove box, put it into the operating chamber of the ball mill. The gas used is argon. Cover the sealing cover to ensure that the tube is in an argon environment. Take it out and put it into the ball mill. The gas used is argon. Cover the sealing cover to ensure that the tube is in an argon environment. Take it out and put it into the ball mill. The ball milling speed is 450 r / min, and it rotates for 60 min each time. Stop for 20 min to dissipate heat. After ball milling for 60 h, VC 0.5 ; S2. In a glove box filled with argon, Co, Cr, Ni, Cu and Fe were mixed in a molar ratio of 1:1:1:1:1 and loaded into a WC cemented carbide ball mill. The ball-to-material mass ratio was 10:1. The rotation speed was 400 r / min and the ball milling time was 30 h. The mill was stopped for 30 min every 5 h to dissipate heat. The raw materials adhering to the grinding balls and the inner wall of the mill were scraped off and mixed every 10 h. Then, the milling was continued to obtain CoCrNiCuFe powder with a particle size of 150 nm or more. S3, mixing: in a glove box filled with argon, weigh 1.933 g of the CoCrNiCuFe powder prepared in step S1, add 0.3888 g of VC prepared in step S2, 0.5 The powder and 7.344 g WC powder were ball-milled for 1 hour, and then 0.334 g cBN powder was added. The ball-to-material mass ratio was 10:1, the rotation speed was 350 r / min, and the ball-milling time was 1 hour. S4, sintering preparation: the mixed material obtained in step S3 is loaded into a graphite mold for pre-compression, the pre-compression pressure is 30 MPa, and the pre-compression is 60 s; then spark plasma sintering is performed, the vacuum degree is 40 Pa, the sintering pressure is 30 MPa, the sintering temperature is 1300 ℃, the heating rate is 50 ℃ / min, and the holding time is 10 min; then the temperature is reduced and the pressure is released to obtain a high entropy alloy / ceramic combined cBN composite material.
[0041] The high entropy alloy / ceramic cBN composite material sample after spark plasma sintering was polished and then tested for structure and performance. The technical parameters of the obtained sintered block are as follows: Example 6
[0042] The raw material formula is weighed according to the following percentages:
[0043] S1. Add 0.2 ml of industrial ethanol as a dispersant to the raw material powder consisting of 5.53 g of vanadium carbide powder and 4.47 g of vanadium powder, and put it into a cemented carbide tank. The ball-to-material ratio is 10:1. The ball milling medium is a cemented carbide ball with a diameter of 8 mm and 5 mm. After repeated gas washing in the transition chamber of the glove box, put it into the operating chamber of the ball mill. The gas used is argon. Cover the sealing cover to ensure that the tube is in an argon environment. Take it out and put it into the ball mill. The gas used is argon. Cover the sealing cover to ensure that the tube is in an argon environment. Take it out and put it into the ball mill. The ball milling speed is 450 r / min, and it rotates for 60 min each time. Stop for 20 min to dissipate heat. After ball milling for 60 h, VC 0.5 ; S2. In a glove box filled with argon, Co, Cr, Ni, Cu and Fe were mixed in a molar ratio of 1:1:1:1:1 and loaded into a WC cemented carbide ball mill. The ball-to-material mass ratio was 10:1. The rotation speed was 400 r / min and the ball milling time was 30 h. The mill was stopped for 30 min every 5 h to dissipate heat. The raw materials adhering to the grinding balls and the inner wall of the mill were scraped off and mixed every 10 h. Then, the milling was continued to obtain CoCrNiCuFe powder with a particle size of 150 nm or more. S3, mixing: In a glove box filled with argon, weigh 1.85 g of the CoCrNiCuFe powder prepared in step S1, add 0.37 g of VC prepared in step S2, 0.5 The powder and 7.05 g WC powder were ball-milled for 1 hour, and then 0.73 g diamond powder was added. The ball-to-material mass ratio was 10:1, the rotation speed was 350 r / min, and the ball-milling time was 1 hour. S4, sintering preparation: the mixed material obtained in step S3 is loaded into a graphite mold for pre-compression, the pre-compression pressure is 30 MPa, and the pre-compression is 60 s; then spark plasma sintering is performed, the vacuum degree is 40 Pa, the sintering pressure is 30 MPa, the sintering temperature is 1150 ℃, the heating rate is 50 ℃ / min, and the holding time is 10 min; then the temperature is reduced and the pressure is released to obtain a high entropy alloy / ceramic combined diamond composite material.
[0044] The high entropy alloy / ceramic bonded diamond composite material sample after spark plasma sintering was polished and then tested for structure and performance. The technical parameters of the obtained sintered block are as follows:
[0045] Experimental data summary: Figure 1 The XRD patterns of the high entropy alloys (CoCrNiCuFe, AlZnCuFeTi and CoNiCuFeMn) with three phase structures provided by the present invention are shown in FIG. Figure 1 As shown: Figure 1a in the middle is AlFeNiCrCu which has both face-centered cubic structure and body-centered cubic structure; Figure 1 b is CoCrNiCuFe with only face-centered cubic structure; Figure 1 In the figure, c is AlZnCuFeTi with only body-centered cubic structure. Generally speaking, typical face-centered cubic (fcc) HEAs have higher plasticity and lower yield strength due to solid solution strengthening and twinning strengthening caused by lattice deformation, while body-centered cubic (bcc) materials often have higher yield strength and lower uniform plastic strain due to insufficient strain hardening ability. Figure 2 and Figure 3 The morphology of the composite sintered bodies of Example 4 and Example 5 respectively shows that the black area is uniformly and densely surrounded by the white area, and a small amount of gray area can be seen in the white area. The gray area and the white area are directly combined and arranged in a staggered manner. The black particles are cBN, the white area is WC, and the gray area is mainly VC. 0.5 The three are mutually dissolved in solid solution, the surface of the sample is smooth, the grains are obvious, and there are no obvious microcracks on the surface. The key to ensuring the quality of cBN composite materials is sintering densification, that is, it is necessary to ensure that there is no significant difference in the expansion degree of the binder and cBN during the liquid phase sintering process, so as to reduce the generation of microcracks inside the sample.
[0046] Figure 4 This is the surface morphology of the composite material of Example 6. It can be clearly seen from Figure a that the black particles are evenly and densely distributed in the gray area, where the black particles are diamonds. It can be seen that the diamond particle sizes are different. The gray area is mainly a WC-based matrix binder, and the high entropy alloy is evenly distributed in the matrix. Figure b is a partial enlarged view of Figure a. It can be seen that the binder wraps the diamond well, and the diamond particle size is between 20-30 μm.
[0047] It can be seen from Examples 1-5 that the sintering temperature, binder ratio and the content of added cBN have a great influence on the performance of the high entropy alloy / ceramic combined cBN composite material. It can be seen from Examples 1-3 that with the increase of sintering temperature, the flexural strength and fracture toughness gradually increase, while the hardness shows a downward trend. The hardness is the highest at 1150 ℃, reaching 1500.15HV, while the flexural strength and fracture toughness gradually increase with the increase of sintering temperature, and the fracture toughness reaches 9.55MPa·m at 1300 ℃. 1 / 2, the flexural strength reaches 866.07 MPa. The increasing trend of flexural strength and fracture toughness is due to the fact that as the set sintering temperature increases, the densification degree of the sintered material increases, thereby improving the performance of the material. It can be seen from Examples 4-5 that as the proportion of high entropy alloy increases, the hardness first decreases and then increases. When the mass fraction of HEA in the binder is 5wt.%, the hardness is the highest at 1528.45 HV, and when the mass fraction of HEA in the binder is 10wt.%, the hardness is the lowest, reaching 1350.8 HV. The fracture toughness has been on an upward trend, and when HEA accounts for 20wt.%, it reaches a maximum of 13.3 MPa·m 1 / 2 , indicating that high entropy alloys are helpful to improve the fracture toughness of composite materials. The flexural strength first increases and then decreases. When the mass fraction of HEA binder is 10wt.%, its flexural strength reaches 866.07 MPa, and the flexural strengths of the other two are also between 550-600 MPa.
[0048] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A high entropy alloy / ceramic combined superhard composite material, characterized in that: The percentage composition of the composite material is: CoCrNiCuFe accounts for 5-15wt.%, 3-10wt.%VC 0.5 and 70-90wt.% WC, the remainder being diamond / cBN; wherein the particle size of the CoCrNiCuFe is less than 150nm; the purity of the WC is greater than 99%, the particle size is less than 150nm, and the particle size of the diamond is 28μm; the high entropy alloy raw material is CoCrNiCuFe, AlZnCuFeTi and CoNiCuFeMn high entropy alloy powders in equal molar ratios, and the non-stoichiometric carbide raw material is TiC prepared by mechanical alloying method 0.4 and VC 0.5 Any one of Ti and TiC mixed powder and V and VC mixed powder prepared by powder or rolling wet grinding method.
2. A method for preparing a high entropy alloy / ceramic combined superhard composite material according to claim 1, characterized in that: The method comprises the following steps: S1, preparation of high entropy alloy, S2, preparation of non-stoichiometric carbide, S3, material mixing, S4, spark plasma sintering, wherein: S1. Preparation of CoCrNiCuFe powder: In a glove box filled with argon, Co, Cr, Ni, Cu and Fe were mixed in a molar ratio of 1:1:1:1:1 and loaded into a WC carbide ball mill. The ball-to-material mass ratio was 10:
1. The rotation speed was 300-600 r / min. The ball milling time was 20-50 h. The mill was stopped for 30 min every 5 h to dissipate heat. The raw materials adhering to the grinding balls and the inner wall of the mill were scraped off and mixed after stopping every 10 h. The milling was continued to obtain CoCrNiCuFe powder with a particle size of 150 nm or finer. S2、VC 0.5 Powder preparation: VC powder and V powder were loaded into a WC carbide ball mill in a glove box filled with argon gas at a mass ratio of 55.3:44.7, with a ball-to-material mass ratio of 10:1-20:1, a rotation speed of 450 r / min, a ball milling time of 60 h, and a 30-min stop for heat dissipation every 5 h to obtain VC 0.5 powder; S3, mixing: in a glove box filled with argon, weigh 5-15wt.% of the CoCrNiCuFe powder prepared in step S1, add 3-10wt.% of VC prepared in step S2, 0.5 The powder and 70-90wt.% WC powder are ball-milled for 1-5 hours, and then 1-5wt.% diamond / cBN powder is added, the ball-to-material mass ratio is 5:1-10:1, the rotation speed is 200-400r / min, the ball milling time is 2-5h, and the machine is stopped for 10min for heat dissipation after every 1h of rotation; S4, sintering preparation: the mixed material obtained in step S3 is loaded into a graphite mold for pre-compression, the pre-compression pressure is 10-30 MPa, and the pre-compression is 60S; then spark plasma sintering is performed, the vacuum degree is 40Pa, the sintering pressure is 30-40MPa, the sintering temperature is 1000-1350°C, the heating rate is 30-100°C / min, and the holding time is 3-30min; then the temperature is reduced and the pressure is released to obtain a superhard composite material combined with a high entropy alloy / ceramic.
3. The method for preparing a high entropy alloy / ceramic combined superhard composite material according to claim 2, characterized in that: The particle size of the V powder is 1-3 μm, and the purity is greater than 99%. The particle size of the VC powder is less than 45 μm, and the purity is greater than 99%.
4. The method for preparing a high entropy alloy / ceramic combined superhard composite material according to claim 2, characterized in that: The purity of the Co, Cr, Ni, Cu and Fe powders is greater than 99%, wherein the particle size of the Co powder is 1-3 μm, the particle size of the Cr powder is less than 75 μm, and the particle size of the other metal element powders is less than 45 μm.
5. The method for preparing the high entropy alloy / ceramic combined superhard composite material according to claim 2, characterized in that: The WC powder has a particle size of 1-3 μm and a purity of more than 99%.
6. The method for preparing the high entropy alloy / ceramic combined superhard composite material according to claim 2, characterized in that: The ball milling processes of steps S1, S2 and S3 all use three types of large, medium and small WC carbide balls with diameters of 8 mm, 5 mm and 2 mm, respectively, wherein the mass ratio of the large, medium and small WC carbide balls is 6:3:
1.
7. The method for preparing a high entropy alloy / ceramic combined superhard composite material according to claim 2, characterized in that: The specific sintering process in step S4 is as follows: first, slowly apply pressure to the sample to 40-50 MPa; then, evacuate to 40 Pa; then, heat from room temperature to 600°C in 5 minutes, and keep at 600°C for 10 minutes; then heat from 600°C to 1000-1350°C at a heating rate of 30-100°C / min, and keep for 3-30 minutes; cool with the furnace to obtain a blank; perform surface grinding and deburring on the prepared blank to obtain a superhard composite material of high entropy alloy / ceramic combination.